(untitled) (IYUNIM: Multidisciplinary Studies in Israeli and Modern Jewish Society, 2026)
In this article, I examine Nathan Alterman’s poetry during the State of Israel’s first decade, while focusing on its divided theopolitical dimension. This division manifests in the two different ways in which he applies theological semantics: on the one hand, he recruits religious language toward legitimizing the Zionist act and its governmental achievements (such as the foundation of the State, Aliyah) as well as its military accomplishments (such as Operation Kadesh). Here, theology serves the national narrative and its ideological justification well. On the other hand, Alterman used theological semantics to validate a moral anti-establishment protest. Theopolitics was utilized to severely criticize the Israeli government’s aggressive practices, especially in relation to underprivileged populations, such as Arabs and Mizrahi Jews. This application articulated the ethos of a moral, humanistic, and universal existence, whilst denouncing the nationalism reflected in state and public conduct. I focus on the poems from "The Seventh Column" as an examination of this divide. After defining the term "Theopolitics," the discussion will continue with a review of poems that exemplify the pro-state aspect, which provides the national act with a metaphoric-religious ’Kosher’ certification. Later, I will examine the critique of the sovereign state and its treatment of minorities. The culmination of this division is presented through Alterman’s criticism of Soviet totalitarianism (the Slánský trial) and an analysis of the poems in City of the Dove. These poems represent a clear anti-governmental use of theological discourse and even dare to present a diasporic stance that prefers the spiritual value of exile over a life of sovereignty and territorial belonging.